Design and sizing of evtol aircraft (development of complex lightweight mechanical actuating devices for eVTOL aircraft - Prototyping & Integration) - Hau, Jun Fei (Nanyang Technological University, 2022)
As the world transits into a more sustainable future, electric vehicles are starting to become the dominant aspect in urban mobility. The idea of electric aircrafts is then born. Sky-high buildings, densely populated cities forbade the installation of long runways and airports. Singapore, for instance, simply could not afford the land space. Electronic Vertical Take-off and Landing (eVTOL) aircrafts is the more probable solution being put out. This concept is known as Urban Air Mobility, leveraging on the vast 3D space for transportation.